Distinctive blood and salivary proteomics signatures in Qatari individuals at high risk for cardiovascular disease - Ghada Yousif; Selvasankar Murugesan; Mohamed Nadhir Djekidel; Annalisa Terranegra; Giusy Gentilcore; Jean Charles Grivel; Souhaila Al Khodor (Scientific Reports)
Abstract Cardiovascular disease (CVD) remains a leading cause of global morbidity and mortality. Timely diagnosis is important in reducing both short and long-term health complications. Saliva has emerged as a potential source for biomarker discovery, offering a non-invasive tool for early detection of individuals at elevated risk for CVD, yet large-scale extensive proteomic analysis using saliva for a comprehensive biomarker discovery remains limited. In an effort to develop a diagnostic tool using saliva samples, our study aims to assess the salivary and plasma proteomes in subjects with high risk of developing CVD using a large-scale proteomic approach. Leveraging on the SOMAscan platform, we analyzed 1,317 proteins in saliva and plasma collected from subjects at a high risk of CVD (HR-CVD) and compared the profiles to subjects with low risk of CVD (LR-CVD). Our analysis revealed significant differences in the plasma and salivary proteins between the two groups. Pathway enrichment analysis of the differentially detected proteins revealed that the immune system activation and extracellular matrix remodeling are the most enriched pathways in the CVD-HR group. Comparing proteomic signatures between plasma and saliva, we found approximately 42 and 17 differentially expressed proteins associated with CVD-HR uniquely expressed in plasma and saliva respectively. Additionally, we identified eight common CVD-risk biomarkers shared between both plasma and saliva, demonstrating promising diagnostic tools for identifying individuals at high risk of developing CVD. In conclusion, saliva proteomics holds a significant promise to identify subjects with a high risk to develop CVD. Further studies are needed to validate our findings.